Study of Variations in Mass Absorption Efficiency of Elemental Carbon Influenced by Different Measurement Techniques and Vehicle Emission - Chen, Dong; An, Zhaojin; Zhao, Qiuyue; Xia, Sijia; Li, Li; Guan, Miao (Frontiers in Environmental Science, 2022)
An inter-comparison study of mass absorption efficiency (MAE) of elemental carbon (EC) by different sampling modes and measurements was conducted at the School of the Environment (SE) and Station for Observing Regional Processes of the Earth System (SORPES) in Nanjing from November 2015 to October 2016. Compared with offline sampling, the underestimation in MAE of online sampling was mainly due to the decreased optical attenuation (ATN) from the losing EC, and the difference in MAEs of the two types of sampling was greatly influenced by secondary organic aerosol (SOA) formation. Based on five temperature protocols, which include four NIOSH-derived protocols and one IMPROVE-A protocol, dependence of MAE on the temperature protocol was investigated. The main reason for the change in MAE estimation was the difference in EC determination. The result showed that low peak inert mode temperature (Tpeak) produced a small amount of pyrolysis carbon, and this carbon fraction was typically classified as organic carbon (OC), resulting in overestimation of EC and thereby underestimation of MAE. In order to study the influence of vehicle emission of highway on MAE values of EC, the simultaneous observation at SE and SORPES was conducted. The mean MAE of SE was 8.5% lower than that of SORPES. EC concentration was estimated to decrease by 0.13 μg/m3 with an increment distance of 100 m. Good correlation was found between the differential ATN for the two sites and the proportion of secondary organic carbon (SOC) at SORPES (R2 = 0.71). These results indicated that high MAE at SORPES was expected to be relevant with the dry deposition of EC from vehicle emission and the lensing effect by SOA coating.